HUMOROUS AND ARTISTIC LANGUAGE STYLE IN THE KITCHEN GOD’S WIFE (Konferensiyalar | Conferences, 2024)
The Kitchen God’s Wife, published in 1989, is the second novel written in by Amy Tan, a Chinese American writer. It delves into the intricate dynamics between a mother and daughter. Beyond the mother-daughter relationship, the novel explores the connections between Winnie and Helen, as well as Auntie Du, and other female characters, making it a noteworthy feminist work that examines the awakening of feminism and contemplations of fate and hope. The book employs a humorous and artistic language style to convey these thematic ideas. Humor is a literary device that aims to generate amusement or laughter. Various devices are employed to create humor, such as hyperbole, exaggeration, incongruity, surprise, sarcasm, irony, and pun. This research endeavors to examine the humor, the use of parallel structure, and the symbolism employed throughout the novel.